Reframing Scale in Competency-Based Continuing Education: The ANCC Outcome-Based Continuing Education Model™ - Jennifer A. Graebe; Evelyn Lengetti (The Journal of Continuing Education in Nursing, 2026)
The American Nurses Credentialing Center Outcome-Based Continuing Education Model™ (ANCC OB-CE Model™) shifts nursing professional development from attendance to demonstrated learning and outcomes. Although scaling credible evidence of professional growth, practice change, and impact is more complex than scaling participation, complexity is not a structural ceiling. Rather, it reflects a maturing accreditation ecosystem capable of broader adoption. This column reframes scale and the ANCC OB-CE Model™.